1994
DOI: 10.1016/0014-5793(94)80472-9
|View full text |Cite
|
Sign up to set email alerts
|

Aequorea green fluorescent protein

Abstract: Expression of the cDNA for Aequorea green fluorescent protein in E. coli yielded a fused protein with fluorescence excitation and emission spectra virtually identical to those of the native green fluorescent protein. Further, a solution of the protein, when mixed with aequorin and calcium ion, emitted a greenish luminescence characteristic of the in vivo luminescence of the animal, indicating a radiationless energy transfer to the protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
83
0
4

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(87 citation statements)
references
References 28 publications
0
83
0
4
Order By: Relevance
“…Photographs were taken by using Kodak Echtachrome 400, and films were subsequently processed to enhance sensitivity. ing GFP in E. coli carrying pHis-AGP at 37°C (9). Strong green fluorescence in single cells was readily detectable under the microscope (data not shown).…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Photographs were taken by using Kodak Echtachrome 400, and films were subsequently processed to enhance sensitivity. ing GFP in E. coli carrying pHis-AGP at 37°C (9). Strong green fluorescence in single cells was readily detectable under the microscope (data not shown).…”
Section: Methodsmentioning
confidence: 95%
“…Molecular cloning and expression of GFP cDNA in Escherichia coli have led to amino acid-sequence determination of the protein and to the location of the chromophore in the primary structure (7,8). GFP expressed in E. coli has also been shown to possess spectroscopic properties identical to the native protein (8)(9)(10). Recent studies have indicated that formation of the chromophore may depend on molecular oxygen or temperature (10)(11)(12).…”
mentioning
confidence: 99%
“…57,58) The emission is due to the presence of a chromophore, formed spontaneously by posttranslational cyclization of the tripeptide Ser65-Tyr66-Gly67 in the protein chain. [59][60][61] It consists of an imidazolone ring structure, and the light emitter is the singlet excited-state of the phenolate anion of the chromophore.…”
Section: Luciferinmentioning
confidence: 99%
“…Advances in the development of proteins conjugated with green fluorescent protein (GFP) have since provided the opportunity for real time optical analysis of protein trafficking events in individual cells (13)(14)(15). Green fluorescent protein is a naturally occurring protein isolated from several different species of jellyfish (Aequoria) and sea cucumbers (Renilla).…”
mentioning
confidence: 99%